2005
DOI: 10.2165/00003088-200544120-00011
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Olmesartan Following Oral Administration of its Prodrug, Olmesartan Medoxomil

Abstract: The population pharmacokinetic analysis of olmesartan showed that: (i) severe renal impairment (serum creatinine >265 micromol/L [approximately 3 mg/dL]) could cause a clearance decrease of > or =30%; (ii) older age, lower bodyweight and being female were determinants of lower clearance but their effects on olmesartan clearance were within 20%; (iii) no statistically significant difference in clearance was found between Westerners and Japanese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 18 publications
1
24
2
Order By: Relevance
“…In the previous population pharmacokinetic analysis of olmesartan after oral administration of its prodrug OM in healthy volunteers and hypertensive patients (Yoshihara et al, 2005), female sex was reported to be one of the effective covariates of a lower apparent oral clearance. However, the observed change was slight and thus not considerable (13.5% lower in women than men) to adjust the dosage.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous population pharmacokinetic analysis of olmesartan after oral administration of its prodrug OM in healthy volunteers and hypertensive patients (Yoshihara et al, 2005), female sex was reported to be one of the effective covariates of a lower apparent oral clearance. However, the observed change was slight and thus not considerable (13.5% lower in women than men) to adjust the dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Minor differences were seen in the pharmacokinetics of olmesartan in Caucasian men and women, with females exhibiting an approximately 10-15% higher AUC and C max than males (Yoshihara et al, 2005), whereas no significant sex difference has been observed in Chinese subjects (Jiang et al, 2009). Although the C max values of olmesartan were similar in elderly compared with young adults, modest accumulation of olmesartan was observed in the elderly with repeated dosing (a 33% increase in AUC corresponding to a 30% reduction in renal clearance) (von Bergmann et al, 2001).…”
Section: E Age Sex and Ethnicitymentioning
confidence: 99%
“…The suspension formulation of olmesartan used in children is bioequivalent to the tablet formulation used in adults. Population pharmacokinetic analysis suggests that the pharmacokinetics of olmesartan do not differ between Western and Japanese populations (Yoshihara et al, 2005).…”
Section: E Age Sex and Ethnicitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is a selective AT1 subtype angiotensin II receptor blocker (6,7), which was recently approved by the US-FDA (8) to treat patients with hypertension. This reduces blood pressure by causing vasodilation and reducing peripheral resistance (9). OLM is also reported to be effective in animal models of atherosclerosis, liver disorders and diabetic nephropathy (10).…”
mentioning
confidence: 99%